Anaerobic batch digestion of cattle manure under various oscillatory flow mixing - Muhammad Nasir, Ismail; Mohd Ghazi, Tinia Idaty; Omar, Rozita; Wan Ab. Karim Ghani, Wan Azlina (Universiti Putra Malaysia Press, 2017)
The feasibility of an anaerobic digestion of cattle manure for biogas production is studied in this paper. A batch thermophilic oscillatory flow anaerobic bioreactor (OFBR) operated in thermophilic (55oC) condition was used. Within the experimental conditions set in this study, the effect of mixing intensity on volatile solids removal was found out to be significant. Results demonstrated that increasing the level of mixing decreased the digester performance. Low intensity mixing at oscillatory Reynolds number (Reo) of 100 achieved an increase of 37% in biogas yields compared to high mixing intensity, Reo of 500. It was observed that the mixing intensity effect interacts with the methane composition in the biogas. The benefit of decreasing mixing intensity emerges to significantly increase the methane composition in the biogas. These experiments established that high intensity mixing was not essential for good performance of oscillatory flow anaerobic bioreactor. In addition, the effect of mixing intensity might be reduced through the use of a slightly lower total solid concentration, hence, lowering the operational cost of the process. Although the study was lab scale a pilot-scale system where mixing retention times are longer would be useful.